Clinical and Pathological Analysis of Patients with Idiopathic Membranous with Elevated Lipids - Li, Miaofang; Zhang, Xiaofeng (Journal of Contemporary Medical Practice, 2025)
Objective: to explore the influencing factors of patients with idiopathic membranous nephropathy accompanied by elevated lipids. Methods: to retrospectively analyze the data of 159 patients with idiopathic membranous nephropathy admitted to Shaanxi Provincial Hospital of Traditional Chinese Medicine from 2021 to 2024, and to compare the differences in clinical and pathological data between patients in the group of patients with elevated blood lipids and patients in the group of patients without elevated blood lipids. Results: Patients in idiopathic membranous nephropathy with elevated lipids group had heavier SUA, Scr and 24h urinary protein, elevated systolic blood pressure, and lower blood ALB than patients without elevated lipids, and the difference was statistically significant (P<0.05). Conclusion: Patients with idiopathic membranous nephropathy with elevated lipids had more severe clinical indicators and elevated systolic blood pressure, and active control of lipid levels may help to improve the prognosis of patients.